Analysis of Efficacy and Safety of Small-Volume-Plasma Artificial Liver Model in the Treatment of Acute-On-Chronic Liver Failure - Li, D; Wang, X; Zhou, J; Duan, Z; Yang, R; Liu, Y; Chen, Y; Zhang, L; Liu, H; Li, W; You, J (Physiological research, 2023)
To explore the efficacy and safety of a small-volume-plasma artificial liver support system (ALSS) in the treatment of acute-on-chronic liver failure (ACLF). A retrospective analysis was performed. All ACLF patients received ALSS of plasma exchange & double plasma molecular absorb system (PE+DPMAS) treatment, and successfully completed this treatment. Patients were divided into small-volume and half-volume plasma groups. We compared the changes of the indicators on liver function, kidney function, blood coagulation function, and blood ammonia level before and after PE+DPMAS treatment; we compared the short-term and long-term curative effects between small-volume and half-volume plasma groups; and the factors influencing Week 4 and Week 12 mortality of ACLF patients were analyzed. The Week 4 improvement rates were 63.96 % and 66.86 % in the small-volume and half-volume plasma groups, respectively. The Week 12 survival rates in the small-volume-plasma and half-volume plasma groups were 66.72 % and 64.61 %, respectively. We found several risk factors affecting Week 4 and Week 12 mortality. Kaplan-Meier survival curves suggested no significant difference in Week 4 and Week 12 survival rates between the small-volume and half-volume plasma groups (P=0.34). The small-volume-plasma PE+DPMAS treatment could effectively reduce bilirubin and bile acids, and this was an approach with high safety and few complications, similar to the half-volume-plasma PE+DPMAS treatment. The small-volume-plasma PE+DPMAS has the advantage of greatly reducing the need for intraoperative plasma, which is especially of importance in times of shortage of plasma.
Keywords: játra umělá; výměna plazmy; Plasma Exchange; retrospektivní studie; lidé; akutní zhoršení chronického selhání jater; jaterní testy; Liver Function Tests; Retrospective Studies; Liver, Artificial; Acute-On-Chronic Liver Failure; Humans